2022
DOI: 10.1007/s00401-022-02454-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide meta-analysis for Alzheimer’s disease cerebrospinal fluid biomarkers

Abstract: Amyloid-beta 42 (Aβ42) and phosphorylated tau (pTau) levels in cerebrospinal fluid (CSF) reflect core features of the pathogenesis of Alzheimer’s disease (AD) more directly than clinical diagnosis. Initiated by the European Alzheimer & Dementia Biobank (EADB), the largest collaborative effort on genetics underlying CSF biomarkers was established, including 31 cohorts with a total of 13,116 individuals (discovery n = 8074; replication n = 5042 individuals). Besides the APOE locus, novel associations with tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 82 publications
0
33
1
Order By: Relevance
“…This finding may first be perceived as counterintuitive, since smaller ventricles is generally thought to indicate less neurodegeneration, and increased CSF P‐tau is generally associated with more neurodegeneration. However, the findings in our current study suggest that the association described by Jansen et al ( 2022 ) may have been confounded by the genetic effects on brain anatomy, causing differences in dilution and concentration across a range of CSF biomarkers. We noted that variants in the GMNC‐OSTN region were common among the CSF pQTLs where ventricular volume had large confounding effects (Fig EV5 ).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This finding may first be perceived as counterintuitive, since smaller ventricles is generally thought to indicate less neurodegeneration, and increased CSF P‐tau is generally associated with more neurodegeneration. However, the findings in our current study suggest that the association described by Jansen et al ( 2022 ) may have been confounded by the genetic effects on brain anatomy, causing differences in dilution and concentration across a range of CSF biomarkers. We noted that variants in the GMNC‐OSTN region were common among the CSF pQTLs where ventricular volume had large confounding effects (Fig EV5 ).…”
Section: Discussioncontrasting
confidence: 63%
“…The results point to ventricle volume as a possible confounder for many CSF pQTL studies, although we demonstrate that most findings remain significant (but sometimes attenuated) after adjustment for ventricle volume. Recently, it was reported that genetic variants in the GMNC‐OSTN region on chromosome 3 (described in detail in this study) were associated both with smaller ventricles and with increased CSF levels of the AD biomarker P‐tau (Jansen et al , 2022 ). This finding may first be perceived as counterintuitive, since smaller ventricles is generally thought to indicate less neurodegeneration, and increased CSF P‐tau is generally associated with more neurodegeneration.…”
Section: Discussionmentioning
confidence: 58%
“…However, a study conducted with healthy volunteers found no correlation between AD core biomarkers and ventricular volume nor the intracranial pressure and CSF production rate [ 39 ]. In a recent genome wide meta-analysis, a link between CSF P-tau 181 , lateral ventricle volume and the genes of GMNC and C16orf95 was established, implying causative relationship for these phenomena [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There continue to be many studies examining CSF for biomarkers of disease. This has been a particular focus in Alzheimer’s disease where studies have examined the correlation between CSF biomarkers and disease pathology [ 66 68 ], examining potential biomarkers that are upregulated before the onset of cognitive impairment [ 69 ] and distinguishing between different types of dementia [ 70 , 71 ]. Apart from β-amyloid (Aβ) and tau proteins, there has been particular interest in microglia-derived sTREM2 (soluble triggering receptor expressed on myeloid cells 2) [ 72 74 ].…”
Section: Elements Of the Blood-csf Barrier And The Csf And Glymphatic...mentioning
confidence: 99%